(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A laboratory experiment was carried out to evaluate the efficacy of threeconcentrations (5 %, 7.5 % and 10 %) of aqueous filtrate of argel (Solenostemma argel)against workers and soldiers of the cotton soil termite (Microtermes thoracalis). Thesynthetic insecticide Morisban 4 was used as a standard. Statistical analysis showedsignificant differences between the tested concentrations of argel aqueous filtrates andMorisban 4 compared with the untreated control. The highest concentration (10%) ofargel aqueous filtrates and Morisban 4 gave 100% mortality for termites. The studyproved the suitability of argel parts for controlling termites, and represents a goodenvironmental and alternative method for synthetic insecticides of termites.